Correction to: Safe injection awareness and practices among nursing staff in an Egyptian and a Saudi hospital - Manal M. Anwar; Alshimaa M. Mohamed Lotfy; Afaf A. Alrashidy (SpringerOpen, 2020)
Following publication of the original article [1], we have been notified that one of the authors' given names is not reflected correctly.